Analysis of the Effect of Shopee Affiliate Marketing on Increasing Consumer Purchase Interest - Tasya Susilawati (Universitas Pendidikan Indonesia (UPI), 2023)
Advances in technology increasingly have an impact on consumer buying interest which is now growing. However, the problem was found in the Shopee marketplace which experienced an error for two days. The purpose of this research is to analyze the technology acceptance model through Shopee affiliate marketing as an effort to increase consumer buying interest. This study uses an associative quantitative approach by collecting data through questionnaires distributed online on social media. The population of this research is Shopee users in Bandung with an age range of 17-30 years with a sample of 210 respondents, but this research managed to collect 215 respondents. The data analysis technique used in this study is a simple linear regression data analysis technique with the help of SPSS tools. The results of this study indicate that Shopee affiliate marketing has a positive and significant effect on purchase intention. This is based on the calculated t value of 8.341 with a significance value of 0.000 where the significance value is less than 0.05 (0.000 0.05). Thus, the better the performance of Shopee Affiliate Marketing on the Shopee marketplace, the higher the consumer's buying interest.